Investors’ response to the #MeToo movement: does corporate culture matter? - Billings, Mary Brooke; Klein, April; Shi, Yanting Crystal (Review of Accounting Studies, 2022)
Abstract This paper provides evidence that the #MeToo movement revised investors’ beliefs about the costs (benefits) of fostering an exclusive (inclusive) culture, as reflected by the absence (presence of a critical mass) of women directors in the board room. Tracking a timeline of events associated with the #MeToo movement that begin with the Harvey Weinstein exposé in October 2017 in the New York Times , we document contrasting market reactions to the movement depending on the existing culture of the firm. Firms that historically excluded women from their board experienced a negative market response as momentum for the cause increased, whereas investors responded favorably to firms that historically embraced the inclusion of women on their boards. In contrast, we do not detect differences in the market’s response to randomly generated pseudo-events during the same time frame when comparing firms with exclusive and inclusive cultures. In the context of increased regulator attention to board gender diversity, as well as the ESG activist campaigns by large institutional investors, our study documents a shift in investors’ beliefs about the risks associated with sexual misconduct and about the value of having women in the boardroom shaping the culture of the firm.